Road flood warning system with information dissemination via social media - Ertie Cusipag Abana; Cindy Verli Dayag; Vanessa Mae Valencia; Princess Hipolito Talosig; John Paulo Ratilla; Gladys Galat (Institute of Advanced Engineering and Science, 2019)
Flooding is one of the most devastating natural disasters in the world. It occurs when water from heavy rains exceeds the capacity of the river banks into which it runs. Some roads are also being affected when this natural phenomenon happens which lead to closure of roads. This closure, however, are often dissiminated late to the people that are passing through the closed roads. For this purpose, a Road Flood Warning System with Information Dissemination via Social Media has been developed to provide timely flood alert information to the public. The system determines the depth of the water through an ultrasonic sensor and disseminates the data gathered to the Internet through the use of social media sites specifically Twitter and Facebook. Moreover, the system has a LED matrix and light emitting diode to display whether the roads are passable during the occurrence of floods. The test results on the performance of ultrasonic sensor showed an accuracy of 98.69% while dissemination of information was 90% successful.